Development of Problem Based Learning Designs Assisted Jobsheet in Learning The Basic of Building Construction Expertise Competence Building Construction, Sanitation and Maintenance at SMK Negeri 1 Sukabumi - Yulia Nurwulan; Dedy Suryadi; Nandan Supriatna (Universitas Pendidikan Indonesia, 2021)
Problem Based Learing (PBL) it’s a learning model thatprepares learners for critical thinking and are able to use theproper means of learning. The purpose of this research is: (1)Carry out the development of design measures PBL assistedjobsheet on basic building Contruction class X KGSP; (2)Knowing the worthiness jobsheet of basic buildingcontruction class X KGSP. This study is research anddevelopment. The research design refers to Sugiyono'smodels which limited to five stages, namely: (1) Potentialand Problems; (2) Data Collection; (3) Product Design; (4)Design Validation; and (5) Design Revision. The type data isqualitative and quantitative. Data collection was carried outbased on the Focus Group Discussion (FGD) and studydocumentation. In this research instrument a questionnairevalidation for product worthiness. The data analysistehniques are descriptive. It is known that studies: (1) Thedesign of PBL assisted jobsheet that refers to general designof syntax PBL; (2) Based on the results of material expertresearch covering aspects of content worthiness, linguistic,serving and benefits, the jobsheet is concluded to fall into avery feasible category. Based on research by media expertscovering the aspect of view, ease of use, consistency, design,and grafting inferable falls into the very feasible category.